2015
DOI: 10.1088/0953-2048/29/1/015015
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of superconductivity in doped graphite and graphene

Abstract: We have observed evidence of superconductivity at temperatures in the vicinity of 260 K in phosphorus-doped graphite and graphene. This evidence includes transport current, magnetic susceptibility, Hall effect and (pancake) vortex state measurements. All of these measurements indicate a transition which is that of a type II superconductor with no type I phase until below the limits of our measurement capabilities. Vortex states are inferred from periodically repeated steps in the resistance versus temperature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 48 publications
0
16
0
Order By: Relevance
“…From the previous work of Larkins et al [56], the consecutive Resistance versus Temperature (R vs. T) measurements of a peeled thin-film of the sample # 023 had shown large and abrupt drops of resistance at high temperatures for a superconductor ( Figure 2.18). Therefore, the sample # 023 was selected to be one of the samples used in this work.…”
Section: Testing Samplesmentioning
confidence: 93%
See 4 more Smart Citations
“…From the previous work of Larkins et al [56], the consecutive Resistance versus Temperature (R vs. T) measurements of a peeled thin-film of the sample # 023 had shown large and abrupt drops of resistance at high temperatures for a superconductor ( Figure 2.18). Therefore, the sample # 023 was selected to be one of the samples used in this work.…”
Section: Testing Samplesmentioning
confidence: 93%
“…Magnetization measurements on thin-film superconductors where the penetration depth is many times greater than the film's thickness have shown that the magnetization is negative and has a "valley" or quasi-parabolic shape as a function of temperature and/or applied field. This is quite different from what can be seen form thick conventional superconductors where pancake vortices are not formed, and the applied magnetic field is expelled from the bulk of the superconductors [56,57,236]. In AC susceptibility measurements [55 -57], the primary differences between thin films where the thickness is considerably less than the magnetic penetration depth and materials with a unity ratio of thickness to penetration depth are…”
Section: Magnetic Characteristics In Thin-film Superconductorsmentioning
confidence: 98%
See 3 more Smart Citations